Online exhaled gas measurements for radiotherapy patients by proton transfer reaction mass spectrometry. (August 2016) - Zou, Xue; Zhou, Wenzhao; Shen, Chengyin; Wang, Hongmei; Lu, Yan; Wang, Hongzhi; Chu, Yannan
Abstract: The present study assessed whether exhaled breath analysis using proton transfer reaction mass spectrometry (PTR-MS) could screen for radiation exposure. As the intensity of proton transfer reaction reagent ion H3 16 O + can be calculated with the intensity of H3 18 O +, the intensity of H3 18 O + was monitored to observe the stability of the PTR-MS instrument during the experiment. The PTR-MS was applied for detecting the volatile organic compounds (VOCs) in the exhaled breath from 42 radiotherapy patients and other 61 patients who had not received radiotherapy. All patients were enrolled in the local cancer hospital. In the experiment, the subjects breathe slowly to the PTR-MS through a direct inlet system without any sampling bag or tube. The breath mass spectrometric data was statistically analyzed using Mann-Whitney U test and stepwise discriminant analysis to find the characteristic ions of radiation exposure. Receiver operating characteristics (ROC) analysis was applied for a combination of the characteristic ions. The PTR-MS instrument was stable as the intensity of reaction ion H3 16 O + was maintained in 1.1%. Through statistically analysis, we found 6 kinds of characteristic ions of radiation exposure, specifically mass-to-charge ratio (m/z) 93, m/z 41, m/z 102, m/z 79, m/z 131, and m/z 143. The sensitivity (true positive rate) and specificity (true negative rate) were 78.6% and 82.0% respectively. The integrated area under the ROC curve (AUC) was 0.869. The results in our study demonstrated the potential of the online breath tester PTR-MS as a non-invasive screening for radiation exposure. Highlights: A fast technology for potentially screening radiation exposure was developed. A direct sampling device, combined with PTR-MS, was used for breath test. The sensitivity and specificity were 78.6% and 82.0% respectively.